Decreased regional homogeneity and increased functional connectivity of default network correlated with neurocognitive deficits in subjects with genetic high-risk for schizophrenia: A resting-state fMRI study. (November 2019) - Ma, Xiaoqian; Zheng, Wenxiao; Li, Chunwang; Li, Zongchang; Tang, Jinsong; Yuan, Liu; Ouyang, Lijun; Jin, Ke; He, Ying; Chen, Xiaogang
Highlights: Subjects at genetic high risk (GHR) for schizophrenia exhibited local abnormalities in the default mode network (DMN), focusing on the fronto-limbic-striatal system. Global functional connectivity was hyperconnected between right superior frontal gyrus (RSFG) and left orbitofrontal gyrus (LOFG) in the DMN among GHR subjects. Cognitive impairments were observed in GHR subjects and regional homogeneity values in RSFG was negatively correlated with long-term memory. Abstract: The complex symptoms of schizophrenia (SCZ) have been associated with dysfunction of the default mode network (DMN). Subjects at genetic high risk (GHR) for SCZ exhibit similar but milder brain abnormalities. This study aimed to investigate functional alterations of DMN from the local to the whole and their relationships with cognitive deficits in GHR subjects. 42 GHR subjects and 38 matched healthy controls (HC) were studied by resting-state functional magnetic resonance imaging (rs-fMRI). Regional homogeneity (ReHo) analysis was performed to measure the local brain function of the DMN, derived by the group independent component analysis, and areas with aberrant ReHo were used as seeds in functional connectivity (FC). Compared with the HC group, the GHR group exhibited significantly decreased ReHo and increased FC in the fronto-limbic-striatal system within the DMN. Furthermore, a significant negative correlation was found between decreased ReHo in the right superior frontal gyrus and the delayed recall in GHR subjects. Our findings revealed decreased local function and hyper-connectivity in the fronto-limbic-striatal system of the DMN in GHR subjects, which is associated with cognitive deficits. This may improve our understanding of the neurophysiological endophenotypes of SCZ and the neural substrate underlying the cognitive deficits of the disease.